Development of Contract Management Strategy to Control Late Payment in Building Projects - Yunianto, Irwan; Rarasati, Ayomi Dita (Journal of International Conference Proceedings, 2020)
Building projects with private ownerss have high level of payment issues (late payment, underpayment, or non-payment). The purpose of this study is to develop a risk-based contract management strategy to avoid late payment from private ownerss to contractors. The research data consisted of literature reviews, questionnaires, and qualitative risk data analyses. The risk analyses identified 10 highest risks as the dominant risk factors from 37 risk variables. The risk response to dominant risk variables was used as a strategy for developing a contract management system. Risks affecting late payment were largely due to contractual clause and contracting clients with less financial capacity due to lack of analysis in the pre-contract phase.